From plastic to elastic stress relaxation in highly mismatched SiGe/Si heterostructures. (1st August 2016) - Isa, Fabio; Salvalaglio, Marco; Dasilva, Yadira Arroyo Rojas; Jung, Arik; Isella, Giovanni; Erni, Rolf; Niedermann, Philippe; Gröning, Pierangelo; Montalenti, Francesco; von Känel, Hans
Abstract: We present a detailed experimental and theoretical analysis of the epitaxial stress relaxation process in micro-structured compositionally graded alloys. We focus on the pivotal SiGe/Si(001) system employing patterned Si substrates at the micrometre-size scale to address the distribution of threading and misfit dislocations within the heterostructures. SiGe alloys with linearly increasing Ge content were deposited by low energy plasma enhanced chemical vapour deposition resulting in isolated, tens of micrometre tall 3D crystals. We demonstrate that complete elastic relaxation is achieved by appropriate choice of the Ge compositional grading rate and Si pillar width. We investigate the nature and distribution of dislocations along the [001] growth direction in SiGe crystals by transmission electron microscopy, chemical defect etching and etch pit counting. We show that for 3 μm wide Si pillars and a Ge grading rate of 1.5% μm −1, only misfit dislocations are present while their fraction is reduced for higher Ge grading rates and larger structures due to dislocation interactions. The experimental results are interpreted with the help of theoretical calculations based on linear elasticity theory describing the competition between purely elastic and plastic stress relaxation with increasing crystal width and Ge compositional grading rate. Graphical abstract: